EPILEPSY – PATHOPHYSIOLOGY, CLINICAL MANIFESTATIONS, AND DIAGNOSTIC APPROACHES - Khakimov M.N. (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: Epilepsy is a chronic neurological disorder characterized by a persistent predisposition to generate epileptic seizures and by the neurobiological, cognitive, psychological, and social consequences of this condition. It affects approximately 50 million people worldwide, making it one of the most common serious neurological diseases. This article reviews the pathophysiological mechanisms underlying epilepsy, its clinical classification, and current diagnostic strategies.